Differences in the Percentages of Students Enrolled in Dual Credit Courses over Time: A Texas, Multiyear Analysis - Moseley, Stacey M.; Slate, John R. (International Journal of Social Learning (IJSL), 2022)
This study aimed to determine the degree to which differences were present in the percentages of all students who enrolled in a dual-credit mathematics course in Texas public high schools by their economic status (i.e., economically disadvantaged and all students). The percentages for both groups of students were compared for the 2014-2015 and the 2015-2016 school years. Inferential statistical analyses revealed statistically significant differences in the percentages in dual-credit mathematics course enrollment for all students and students who were economically disadvantaged in both the 2014-2015 and the 2015-2016 school years. For both years, economically disadvantaged students had a lower enrollment rate in dual-credit mathematics courses than all students' percentage enrollment in dual-credit mathematics courses. Implications of these findings, as well as recommendations for future research, were discussed.